Characterization of systemic disease in primary Sjögren's syndrome: EULAR-SS Task Force recommendations for articular, cutaneous, pulmonary and renal involvements. (31st July 2015) - Ramos-Casals, Manuel; Brito-Zerón, Pilar; Seror, Raphaèle; Bootsma, Hendrika; Bowman, Simon J.; Dörner, Thomas; Gottenberg, Jacques-Eric; Mariette, Xavier; Theander, Elke; Bombardieri, Stefano; De Vita, Salvatore; Mandl, Thomas; et al.
Abstract: Objective. To reach a European consensus on the definition and characterization of the main organ-specific extraglandular manifestations in primary SS. Methods. The EULAR-SS Task Force Group steering committee agreed to approach SS-related systemic involvement according to the EULAR SS Disease Activity Index (ESSDAI) classification and proposed the preparation of four separate manuscripts: articular, cutaneous, pulmonary and renal ESSDAI involvement; muscular, peripheral nervous system, CNS and haematological ESSDAI involvement; organs not included in the ESSDAI classification; and lymphoproliferative disease. Currently available evidence was obtained by a systematic literature review focused on SS-related systemic features. Results. The following information was summarized for articular, cutaneous, pulmonary and renal involvement: a clear, consensual definition of the clinical feature, a brief epidemiological description including an estimate of the prevalence reported in the main clinical series and a brief list of the key clinical and diagnostic features that could help physicians clearly identify these features. Unfortunately we found that the body of evidence relied predominantly on information retrieved from individual cases, and the scientific information provided was heterogeneous. The analysis of types of involvement was biased due to the unbalanced reporting of severe cases over non-severe cases, although the main sources of bias were the heterogeneous definitions of organ involvement (or even the lack of definition in some studies) and the heterogeneous diagnostic approach used in studies to investigate involvment of each organ. Conclusion. The proposals included in this article are a first step to developing an optimal diagnostic approach to systemic involvement in primary SS and may pave the way for further development of evidence-based diagnostic and therapeutic guidelines.